A new species of Sphaeronemoura (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2020)
A new amphinemurine nemourid species, Sphaeronemoura acutispina sp. n. is reported from Guangxi Zhuang Autonomous Region of southern China and is compared to its most similar congener.